ANALISIS KEMANDIRIAN KINERJA PENGELOLAAN KEUANGAN DAERAH PROVINSI SUMATERA SELATAN - Roswaty Roswaty (Universitas Indo Global Mandiri)
South Sumatra is a province that consists of 13 Districts and 4 Cities. South Sumatra formally implement autonomy in 2004 set out in the legislation. Autonomy basically aims to provide greater opportunities for the regions to conduct financial management in particular regions. The construction has been done in South Sumatra Province can not be separated from central government grants to help regional development. The level of financial management independence showed that a region has gone well with maximizing resources to develop the region. Based on the data collected showed that The level of financial management independence South Sumatra province average is still a low level of self-sufficiency. Low levels of financial capability to finance its own activities of government in governance, development, and service to the community. Moreover, it can also mean that there are no significant improvements in terms of community participation in local development, namely in terms of payment of taxes and levies. Key words : Autonomy, Financial Management Independence, South Sumatra, public Sector Financial Management